Misi Penginjilan Paulus: Pandangan Moderasi Beragama Dan Inklusivitas - Yorivo Yorivo; Mentari Dwifani; Elsa Lorensa; Sri Wahyuni (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This paper explores the views of religious moderation and inclusivity in the evangelizing mission of Paul, a major apostle in early Christian society. Through analysis of Paul's letters, especially those related to evangelism, this paper aims to understand how the principles of religious moderation, inclusive attitudes, and the love of Christ became the foundation of Paul's mission of evangelism. This paper also explores the relevance of these principles in the context of evangelism in the modern era. The Apostle Paul's views on religious moderation in the context of evangelistic missions, with a primary focus on the central role of Christ's love in shaping and supporting early Christian evangelistic efforts. Through analysis of Paul's letters, research findings highlight that the views of moderation and inclusiveness promoted by Paul reflect the principles of unconditional love. The love of Christ, at the center of Paul's views, is not only a theological theme but also an intrinsic attraction that influences the hearts and souls of individuals. Paul's inclusive and moderate attitude formed the foundation of a Christian community that was open and welcoming to all levels of society. The implications of this view are highly relevant in designing modern evangelistic strategies that incorporate the love of Christ as a central force.